PENGARUH PRENATAL YOGA TERHADAP KETIDAKNYAMANAN PADA IBU HAMIL TRIMESTER III DI PUSKESMAS PARGARUTAN TAHUN 2020 - Dewi, Sri Sartika Sari; Napitupulu, Mastiur; Nasution, Ismayanti (Jurnal Kesehatan Ilmiah Aufa Royhan, 2020)
The discomfort that is often felt by pregnant women in the trimester such as frequent urination, diﬃculty sleeping, shortness of breath and back pain, fatigue and leg cramps that are often felt at night. The purpose of this study was to determine the effect of prenatal yoga on discomfort in third trimester pregnant women at Pargarutan Health Center. The type and design of the research was quantitative with a pre-experimental analytical design with a pretest-post test one group design approach. The population was all pregnant women in the third trimester at Pargarutan Health Center totaling 25 people, the sampling technique was the total population. Data analysis was univariate analysis and bivariate analysis with dependent T test. The conclusion showed that before doing prenatal yoga, the average discomfort for pregnant women in the third trimester was 1.560. After doing prenatal yoga, the average discomfort for pregnant women in the third trimester was 1.160. There is an effect of prenatal yoga on discomfort in third trimester pregnant women at Pargarutan Health Center with p value = 0.001 <α = 0.05. Midwives in carrying out pregnancy care should apply prenatal yoga in pregnant women classes so that pregnant women can do prenatal yoga independently.